MENUJU INDONESIA YANG BERMAKNA: Analisis Tekstual-Empiris terhadap Pemikiran Charles Taylor tentang Politik Pengakuan dan Multikulturalisme, serta Kemungkinan Penerapannya di Indonesia. - Reza A.A Wattimena (Litbang STFT Widya Sasana Malang, 2011)
Inspired by Charles Taylor’s Political Philosophy, the author will argue that to become a meaningful society, Indonesian society first of all has to respect various forms of life in the society. The various forms of life have to live authentically according to its identity, value, and customs in relation with other forms of life that co-exist in the society. The author will also try to apply Taylor’s political philosophy in the context of Indonesian society. In the end, Indonesian context can give certain critical remarks to the development of Taylor’s philosophy